2019
DOI: 10.4236/aid.2019.93020
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Practice against Malaria and Associated Factors in the City of Parakou in Northern Benin: Results of a Population Survey in 2017

Abstract: Introduction: Self-medication is a common practice in Benin. It has many consequences on people's health in general and develops chemoresistance in particular. Aim: The aim of this work is to study the practice of anti-malarial self-medication in the city of Parakou and to identify the associated factors with this practice. Methods: This was a descriptive cross-sectional analytical survey that took place in the period from April 15 to June 24, 2017. Adults who reported having had malaria symptoms in the last 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Similar findings were also observed in the studies done in Kenya, Benin and Ghana, where self-medication is still practised in these counties and Tanzania is no different. 32,33 Furthermore, we found that patients from high endemic facilities, who are male, and those who come with high fever, headache, abdominal pain, joint pain, general body malaise, and vomiting symptoms have a high chance of being diagnosed with malaria. This finding aligns with the Tanzania malaria diagnosis guideline, where the guideline also identifies the symptoms observed in this study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar findings were also observed in the studies done in Kenya, Benin and Ghana, where self-medication is still practised in these counties and Tanzania is no different. 32,33 Furthermore, we found that patients from high endemic facilities, who are male, and those who come with high fever, headache, abdominal pain, joint pain, general body malaise, and vomiting symptoms have a high chance of being diagnosed with malaria. This finding aligns with the Tanzania malaria diagnosis guideline, where the guideline also identifies the symptoms observed in this study.…”
Section: Discussionmentioning
confidence: 91%
“…13 This is further compounded by the practice of self-medication which has been described as a significant hindrance to proper disease management in many developing countries. [14][15][16][17] Recently, in Tanzania, the "not every fever is Malaria" campaign aims to educate people that not every fever episode experienced requires an antimalarial. 18 Other diseases such as typhoid, dengue, chikungunya, and urinary tract infections present the same symptoms as malaria.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the time, out-of-pocket expenses were required, despite the availability of some of the drugs for free in public health facilities. This is because of the requested payments for medical consultation and lab exams before obtaining the drug for free; the poorest of the population prefer to spend the little money they have to buy medicines instead, and thus resort to self-medication [ 20 ]. In addition, in contrast with the recommendations, the most frequently used drug remains quinine, which is not provided for free.…”
Section: Discussionmentioning
confidence: 99%
“…In most developing countries, proper diagnosis of malaria has been a challenge due to the lack of testing equipment, few personnel to run diagnostic tests, and patients' self-medicating [32]- [34]. Machine learning can relieve this burden by providing a high-accuracy disease prediction tool that doesn't require expensive equipment or trained personnel to run.…”
Section: Discussionmentioning
confidence: 99%